2012
DOI: 10.1177/1557988312456697
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of the Human Papillomavirus Vaccine Among Urban Adolescent Males

Abstract: The human papillomavirus (HPV) vaccine was recently approved for use in males. Certain groups, such as men who have sex with men (MSM), are at increased risk of HPV infection. The purpose of the study was to understand perceptions of HPV and the vaccine among adolescent and young adult males, both heterosexual and MSM. Seventy-six males (45 heterosexual, 31 MSM) completed a questionnaire and participated in a focus group. Overall, 42% had heard of HPV and 39% had heard of the HPV vaccine. Males had moderate to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 27 publications
1
38
0
5
Order By: Relevance
“…The majority of participants were white, either in education or already holding a higher degree, and living in urban areas. Participants were aged between 16 and 71 years, three studies targeted MSM below the age of 26 33 36 39. Participants were mainly recruited via convenience sampling within large urban areas: gay community events and meeting points (7), sexual health clinics (4), universities (3) and population-based panels (2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of participants were white, either in education or already holding a higher degree, and living in urban areas. Participants were aged between 16 and 71 years, three studies targeted MSM below the age of 26 33 36 39. Participants were mainly recruited via convenience sampling within large urban areas: gay community events and meeting points (7), sexual health clinics (4), universities (3) and population-based panels (2).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported that MSM believed HPV vaccination would be good, safe, smart, easy, important and harmless 33 39. In general, MSM considered the HPV vaccine effective in preventing HPV-related diseases, with one study indicating lower perceived effectiveness in preventing genital warts than cancers 40.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, unvaccinated adolescents have low awareness compared with their vaccinated counterparts [52]. However, among urban adolescent males, those who are homosexual are more knowledgeable about the HPV vaccine than heterosexual adolescent males [53].…”
Section: Lack Of Awareness Among Parents and Adolescentsmentioning
confidence: 98%
“…[29][30][31] Unfortunately all these issues among young males have only been studied to a limited extent. [32][33][34][35][36] Specifically in Italy, few studies have been conducted among different groups, [37][38][39] but to the authors' knowledge little is known to date regarding HPV vaccination in young males. It remains imperative this evaluation in order to identify information needs and to design future strategies for expanding cancer prevention.…”
Section: Introductionmentioning
confidence: 99%